Negotiating Environmental Sovereignty in Costa Rica. Issue 2 (15th March 2013) - Graef, Dana J.; Wolford, Wendy; Borras, Saturnino M.; Hall, Ruth; Scoones, Ian; White, Ben
ABSTRACT This article analyses the linked histories and changing national discourses surrounding a transnational mining concession and subsequent plans for hydroelectric development in Costa Rica. The analysis shows how project framing shifted from un‐environmental to green, paralleling a change in public debate from defence against a transnational threat to support of national sovereignty. Dissenters questioned an imperial project that would preclude the state and its citizens from the benefits of industrial development; now the problem is recalled as extractive development itself. Thus popular protests against the mine have come to be remembered as a defence of the nation's environment. This article defines environmental sovereignty as a relational concept that decentres human dominion. In addition, it argues for increased scholarly attention to unimplemented development. This case demonstrates how land deals transcend their own boundaries in time, space and imagination.